THE EFFECTS OF CORPORATE RESTRUCTURING ON AGGREGATE INDUSTRY SPECIALIZATION - Hatfield, Donald E.; Liebeskind, Julia Porter; Opler, Tim C. (Strategic Management Journal, 1996)
It has been widely argued that the purpose of corporate restructuring during the 1980s was to produce a population of more industry-specialized, competitive firms in response to intensifying global competition. A number of studies show that corporate restructuring resulted in increased corporate focus during the 1980s. However, no study has yet examined whether corporate restructuring resulted in increased specialization at the industry level during the 1980s. This study examines this issue. First, we examine whether or not aggregate industry specialization increased during the 1980s. That is, we ask: did the average firm in any given U.S. industry become more or less specialized to that industry during the 1980s? Second, we examine whether corporate restructuring was a significant determinant of change in aggregate industry specialization during the 1980s. Using a sample of 686 four-digit SIC industries and 64 two-digit industry groups, this study finds that aggregate industry specialization declined very slightly at both the four-digit and two-digit level between 1981 and 1989. This study also finds that sell-offs of establishments through corporate control transactions or interfirm asset sales had no significant effect on aggregate industry specialization.